Hybrid Dataflow/von-Neumann Architectures - Yazdanpanah, Fahimeh; Alvarez-Martinez, Carlos; Jimenez-Gonzalez, Daniel; Etsion, Yoav (IEEE transactions on parallel and distributed systems, 2014)
General purpose hybrid dataflow/von-Neumann architectures are gaining attraction as effective parallel platforms. Although different implementations differ in the way they merge the conceptually different computational models, they all follow similar principles: they harness the parallelism and data synchronization inherent to the dataflow model, yet maintain the programmability of the von-Neumann model. In this paper, we classify hybrid dataflow/von-Neumann models according to two different taxonomies: one based on the execution model used for inter- and intrablock execution, and the other based on the integration level of both control and dataflow execution models. The paper reviews the basic concepts of von-Neumann and dataflow computing models, highlights their inherent advantages and limitations, and motivates the exploration of a synergistic hybrid computing model. Finally, we compare a representative set of recent general purpose hybrid dataflow/von-Neumann architectures, discuss their different approaches, and explore the evolution of these hybrid processors.